Estilos de enseñanza de los docentes y estilos de aprendizaje de los estudiantes de la Institución Educativa N° 60080 Carlos Patricio Olórtegui Saenz de nivel secundario, Ramón Castilla 2022 - Palomino Lavi, Irving Sandrito (2024)
The central objective of the study was to determine the relationship that exists between the teaching styles of the teachers and the learning style of the students of the I.E. 60080 Carlos Patricio Olórtegui Saenz secondary level of Ramon Castilla 2022. The research was guided by a quantitative approach of correlational scope and a non-experimental cross-sectional design, it included a sample of 240 secondary school students who were surveyed using the teaching styles and learning styles. The results determined that the high and low levels represent 52.08%, which shows a direct relationship between both variables. This result was confirmed by Kramer's V statistic as 0725, demonstrating a high correlation between the teacher's teaching style and the teacher's teaching style. of student learning. The study concluded the existence of a considerable association between the teaching styles of the teachers and the learning styles of the students at the institution analyzed.